Fast periodic presentation of natural images reveals a robust face-selective electrophysiological response in the human brain - Rossion, B.; Torfs, K.; Jacques, C.; Liu-Shuang, J. (Journal of vision (Charlottesville, Va.), 2015)
We designed a fast periodic visual stimulation approach to identify an objective signature of face categorization incorporating both visual discrimination (from nonface objects) and generalization (across widely variable face exemplars). Scalp electroencephalographic (EEG) data were recorded in 12 human observers viewing natural images of objects at a rapid frequency of 5.88 images/s for 60 s. Natural images of faces were interleaved every five stimuli, i.e., at 1.18 Hz (5.88/5). Face categorization was indexed by a high signal-to-noise ratio response, specifically at an oddball face stimulation frequency of 1.18 Hz and its harmonics. This face-selective periodic EEG response was highly significant for every participant, even for a single 60-s sequence, and was generally localized over the right occipitotemporal cortex. The periodicity constraint and the large selection of stimuli ensured that this selective response to natural face images was free of low-level visual confounds, as confirmed by the absence of any oddball response for phase-scrambled stimuli. Without any subtraction procedure, time-domain analysis revealed a sequence of differential face-selective EEG components between 120 and 400 ms after oddball face image onset, progressing from medial occipital (P1-faces) to occipitotemporal (N1-faces) and anterior temporal (P2-faces) regions. Overall, this fast periodic visual stimulation approach provides a direct signature of natural face categorization and opens an avenue for efficiently measuring categorization responses of complex visual stimuli in the human brain.